Development and evaluation of an online three-level proton vs photon decision support prototype for head and neck cancer – Comparison of dose, toxicity and cost-effectiveness. Issue 2 (February 2016) - Cheng, Qing; Roelofs, Erik; Ramaekers, Bram L.T.; Eekers, Daniëlle; van Soest, Johan; Lustberg, Tim; Hendriks, Tim; Hoebers, Frank; van der Laan, Hans Paul; Korevaar, Erik W.; Dekker, Andre; Langendijk, Johannes A.; et al.
Abstract: To quantitatively assess the effectiveness of proton therapy for individual patients, we developed a prototype for an online platform for proton decision support (PRODECIS) comparing photon and proton treatments on dose metric, toxicity and cost-effectiveness levels. An evaluation was performed with 23 head and neck cancer datasets.